Екологічна небезпека відпрацьованих мастильно-охолоджувальних рідин - Гарячевська, Д. В. (ХНУРЭ, 2012)
In a study of environmental hazards lubricating fluids. The method of testing on Daphnia assessed the negative impact of waste metalworking fluids on the environment and the requisite amount of pure water to dilute the contaminated coolant to safe levels for aquatic organisms.
Keywords: екологічна небезпека